Subnational variations in resilience strategies to adverse contexts in global value chains: evidence from Pakistani offshoring services providers - Choksy, Umair Shafi; Gölgeci, Ismail; Khan, Muhammad Naveed; Khan, Zaheer; Shi, Xiaohui (Leo); Mirza, Zarak (Emerald, 2025)
Purpose Drawing upon research in global value chains (GVCs), resilience and subnational regions, this study aims to examine how suppliers from different subnational regions operating in adverse contexts differ in successfully meeting GVC buyers’ demands and becoming resilient. Design/methodology/approach This study adopted a qualitative research approach relying on 34 in-depth interviews with senior managers of offshoring service providers (OSPs) across two subnational regions in Pakistan – Karachi and Lahore. This study complemented the qualitative analysis with the fuzzy-set qualitative comparative analysis (fsQCA) technique to triangulate, enhance validity and identify causal configurations. Findings The results reveal that OSPs from different subnational regions adopt different approaches to tackle challenges arising from political instability and violence. GVC governance structures vary across subnational regions and, in turn, shape OSPs’ resilience strategies. Karachi-based OSPs, influenced by adaptive modular governance, exhibit local agency-driven resilience, characterised by robustness and technological adaptiveness to address any direct impact of political instability. In contrast, Lahore-based OSPs, operating under relational and captive governance, adopt reputation-driven resilience, emphasising visibility and agility to mitigate any client concerns associated with country image and enhance trust with international clients. The fsQCA provided nuanced insights into the different combinations and configurations of resilience strategies that lead to successful product delivery. Originality/value This study contributes to the conceptualisation of disadvantaged supplier resilience as a continuous, practice-based response to adverse context, rather than a time-bound capability. Furthermore, it contributes to the emerging international business literature on adaptive GVC governance by demonstrating how suppliers in adverse subnational contexts actively shape governance dynamics from below, rather than passively receiving coordination from above. Last, it deepens the literature on subnational heterogeneity by illustrating how exposure to political instability and violence produces divergent resilience repertoires among GVC suppliers.
Keywords: GVC governance adaptation; Resilience; Adverse contexts; Subnational regions; fsQCA Pakistan; Karachi; Lahore; fi=Kansainvälinen liiketoiminta|en=International Business|; fi=Kansainvälinen liiketoiminta|en=International Business|